A Comparative Study of Total Quality Management (TQM) Implementation in Islamic Educational Institutions - Muhammad Nauval Izzul Kamal; Badrul Mudaris (Journal of Educational Management Research, 2026)
This study aims to compare the implementation of Total Quality Management (TQM) in Islamic educational institutions by examining similarities and differences in the aspects of planning, implementation, and evaluation of educational quality. The research employs a descriptive qualitative approach, with data collected through in-depth interviews, observations, and documentation to capture both managerial practices and institutional values. The findings indicate that TQM is implemented through two distinct approaches: a systematic and modern model that emphasizes structured management and data-driven decision-making, and a traditional approach that prioritizes moral development and spiritual values. Despite these differences, both approaches share a common objective of improving educational quality based on Islamic principles. Furthermore, the study highlights that the integration of professional management practices with strong spiritual foundations creates a more comprehensive and sustainable quality management system. It implies that the success of TQM in Islamic education depends on balancing managerial effectiveness and spiritual commitment as a unified framework for continuous improvement.